2004
DOI: 10.1128/iai.72.1.546-558.2004
|View full text |Cite
|
Sign up to set email alerts
|

The ADP Ribosyltransferase Domain of Pseudomonas aeruginosa ExoT Contributes to Its Biological Activities

Abstract: ExoT is a type III secreted effector protein found in almost all strains of Pseudomonas aeruginosa and is required for full virulence in an animal model of acute pneumonia. It is comprised of an N-terminal domain with GTPase activating protein (GAP) activity towards Rho family GTPases and a C-terminal ADP ribosyltransferase (ADPRT) domain with minimal activity towards a synthetic substrate in vitro. Consistent with its activity as a Rho family GTPase, ExoT has been shown to inhibit P. aeruginosa internalizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
83
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(83 citation statements)
references
References 54 publications
0
83
0
Order By: Relevance
“…Crucial to its success as a human opportunistic pathogen is its ability to inhibit epithelial wound repair. Previously published studies have demonstrated that the GAP and ADPRT domains of ExoT work together to inhibit cell migration, a key step in epithelial wound repair (17,18). We now show that these domain activities also combine to effectively block cell division, another important cellular process in wound repair, by targeting cytokinesis at multiple steps.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…Crucial to its success as a human opportunistic pathogen is its ability to inhibit epithelial wound repair. Previously published studies have demonstrated that the GAP and ADPRT domains of ExoT work together to inhibit cell migration, a key step in epithelial wound repair (17,18). We now show that these domain activities also combine to effectively block cell division, another important cellular process in wound repair, by targeting cytokinesis at multiple steps.…”
Section: Discussionmentioning
confidence: 52%
“…We have previously demonstrated that P. aeruginosa inhibits the repair of wounded epithelium in an ExoT-dependent manner (17,18). In this article, we report that P. aeruginosa inhibition of wound repair is in part due to its inhibition of host-cell division by targeting cytokinesis at multiple steps.…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…To distinguish between these possibilities, we complemented PA103 DUDT with a pUCP20 expression vector harbouring either the wild-type ExoT or its inactive form ExoT(R149K, AAA) that has been shown to be secreted through the T3SS (Garrity-Ryan et al, 2004). PA103 DUDT+pExoT and PA103 DUDT+pExoT (R149K, AAA) strains were both highly sensitive to CA-AMF antimicrobial activity in the CM (Fig.…”
Section: Ca-amf Antimicrobial Activity Requires a Functional T3ssmentioning
confidence: 99%
“…The pUCP20 : : pscJ was transformed into PA103 pscJ : : Tn5 bacteria which were made competent as described by Chuanchuen et al (2002). pUCP20 : : exoT and pUCP20 : : exoT(R149K, AAA) have been described previously described (Garrity-Ryan et al, 2004).…”
Section: Introductionmentioning
confidence: 99%